2016
DOI: 10.1177/0021934716658863
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Mainstream Success

Abstract: The bulk of sociological work examines African American men who are young, unemployed, and poorly educated. In contrast, we offer a nuanced look at Black men living and working in mainstream society—men in the American mainstream although not always identifying as middle class. From 25 in-depth interviews, our data show an apparent contradiction. We find that men account for their success through their individual choices and declared personal motivation to succeed. Yet, throughout their interviews, these men r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…As a result of their social support and networks, some participants were encouraged to pursue a university education or start a small business. Similarly, other research on young Black men from low-income communities, found that social supports offered young men diverse social networks that developed their life skills, employability and access to job opportunities and extracurricular activities (Wiebold & Spiller, 2017).…”
Section: Building Collective Resilience: Social Support and Educationmentioning
confidence: 86%
“…As a result of their social support and networks, some participants were encouraged to pursue a university education or start a small business. Similarly, other research on young Black men from low-income communities, found that social supports offered young men diverse social networks that developed their life skills, employability and access to job opportunities and extracurricular activities (Wiebold & Spiller, 2017).…”
Section: Building Collective Resilience: Social Support and Educationmentioning
confidence: 86%